Parental engagement and academic transparency through mobile information systems in vocational education - W Wagino; Alfridho Leoparlin; Wawan Purwanto; M Giatman (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
The manual management of teacher journals, agendas, and student attendance in Indonesian vocational schools (SMK) often limits real-time information access for parents, resulting in one-way communication and limited academic transparency. This study aimed to develop and evaluate DIJAGA, a mobile-based academic information system integrating teacher journals, student attendance, and parental monitoring. The Research and Development (R&D) method using the ADDIE model was employed. The study involved one media expert, two content experts, 43 teachers, 124 parents, and attendance data from 180 students. Data were collected through expert validation, practicality and effectiveness questionnaires, and a one-group pretest-posttest attendance assessment. The results showed high validity, with mean Aiken's V values of 0.833 for media and 0.816 for content. DIJAGA was considered practical by 95% of teachers and 91% of parents, while the effectiveness score reached 80.41%. Student attendance increased from 87.22% to 92.05%, with a significant paired-samples t-test result, t(179) = 6.975, p < .05. The N-Gain score was 0.378 (moderate), and Cohen's d was 0.520 (moderate). These findings indicate that DIJAGA is a valid, practical, and potentially effective system for improving academic transparency, parental trust, communication, and student attendance. However, because the study used a one-group pretest-posttest design without a comparison group, the findings should be interpreted as exploratory evidence of feasibility rather than definitive causal evidence.